2004
DOI: 10.1038/sj.onc.1208168
|View full text |Cite
|
Sign up to set email alerts
|

Signaling properties and expression in normal and tumor tissues of two phospholipase C epsilon splice variants

Abstract: Phospholipase Ce (PLCe) is a novel member of phosphoinositide-specific phospholipase C enzymes with a unique regulatory link to Ras GTP-ases. In the present studies, we establish existence of two splice variants (PLCe1a and PLCe1b) derived from human PLCe1 gene. When expressed in COS or HEK293 cells, PLCe1a and PLCe1b have similar potential to be stimulated by diverse signaling pathways via tyrosine kinase and G-protein coupled receptors and share the ability to function as an effector of Ras. The expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 35 publications
3
45
1
Order By: Relevance
“…But there are a number of genes that use alternative splicing to generate several numbers of isoforms. Alternative splicing variants have been previously reported for several of PLC isozymes including rat PLC-β1 (39), human PLC-β2 (40), rat PLC-β4 (41), rat PLC-δ4 (33), and human PLC-ε (42). Here, we analyzed and identified additional splicing variants for PLC isozyme using BLAST server in mouse species.…”
Section: Diverse Splicing Variants Of Plcsmentioning
confidence: 99%
See 1 more Smart Citation
“…But there are a number of genes that use alternative splicing to generate several numbers of isoforms. Alternative splicing variants have been previously reported for several of PLC isozymes including rat PLC-β1 (39), human PLC-β2 (40), rat PLC-β4 (41), rat PLC-δ4 (33), and human PLC-ε (42). Here, we analyzed and identified additional splicing variants for PLC isozyme using BLAST server in mouse species.…”
Section: Diverse Splicing Variants Of Plcsmentioning
confidence: 99%
“…Two splicing variants of human PLC-ε with a different N-terminal region have been reported (42), but mouse PLC-ε isozyme was found to have two novel splicing variants in a different region. Surprisingly, mouse PLC-ε1c lacks the Ras-GEF domain and partial PH domain at the N-terminus.…”
Section: Diverse Splicing Variants Of Plcsmentioning
confidence: 99%
“…Alternative splicing variants have been reported for several of PI-PLC isozymes, including human and rat PI-PLC ␤ 1, human PI-PLC ␤ 2, rat PI-PLC ␤ 4, rat PI-PLC ␦ 4, and human PI-PLC (47)(48)(49)(50)(51)(52).…”
Section: Splicing Variants Of Pi-plcmentioning
confidence: 99%
“…Three splicing variants of the human PI-PLC 1 gene have been reported, with the second variant showing a different N-terminal region, and the third variant using an alternate in-frame splice site in the coding region that results in a shorter protein ( 52 ).…”
Section: Splicing Variants Of Pi-plcmentioning
confidence: 99%
“…Hence, PLCE1 plays a crucial role in regulating cell growth, differentiation, apoptosis and angiogenesis (15). It was previously demonstrated that PLCE1 was involved in the development and progression of various cancers, including esophageal cancer (3,10,(16)(17)(18)(19)(20)(21)(22). In addition, the expression of PLCE1 was associated with the survival of patients with esophageal cancer (23,24).…”
Section: Introductionmentioning
confidence: 99%